PERBANDINGAN PLYOMETRIC EXERCISE DENGAN RESISTANCE EXERCISE TERHADAP PERFORMA OTOT LOWER EXTREMITY PADA PEMAIN SEPAK BOLA : Literature Review - Gusdiartomo (2021)
Muscle performance is an important component in soccer players for supporting appearance during matches. Plyometric and resistance exercise are 2 types exercises that can improve muscle performance. The purpose of this study is to review scientific articles that examine the comparison of the effect plyometric and resistance exercise on muscle performance soccer players. This study uses a literature review study method. The search of the scientific articles was carried out on PubMed, Google scholar, Science Direct, PEDro, Elsevier. The scientific articles that will be studied are it were discussing for the effects of plyometric and resistance exercise on muscle performance soccer players which published ranging 2016-2020. From the search results, there are 5 scientific articles that meet the criteria and will then be studied. The result of the study from five scientific articles, there are 3 scientific articles which showed that resistance exercise article more effective than plyometric exercise, 1 scientific article revealed that both plyometric and resistance exercises were equally effective. 1 scientific article showed plyometric exercise more effective compared to resistance exercise.